‘Ex-Pagan Pagans’?: Paul, Philo, and Gentile Ethnic Reconfiguration - McDonald, Denys N. (Journal for the study of the New Testament, 2022)
In Paul: The Pagans’ Apostle (2017), Paula Fredriksen reminds us that gods and their cults were intertwined with ancient ethnic groups so much so that, when Gentiles committed themselves exclusively to Israel’s God, some Jews considered this ‘tantamount to changing ethnicity’. Fredriksen claims, however, that Paul’s Gentile addressees – whom she terms ‘ex-pagan pagans’ – remain separate ethnically from Jews despite forsaking their ancestral gods for Israel’s. Given that gods and ethnicity were intertwined, this article examines if it is reasonable to conclude that Paul thinks Gentile Christ-followers remain strictly Gentiles after they have abandoned their ethnic gods and entered into a relationship with Israel and its God. I argue that, similar to Philo’s proselyte inclusion strategy, Paul incorporates Gentiles-in-Christ into ethnic Israel. As Abraham’s ‘offspring’, Paul suggests that his addressees not only gain membership in Israel’s covenant on account of Israel’s messiah, but that they also acquire a new ethnic identity despite that their prior identities as ‘the Gentiles’ are not erased. This study, then, seeks to destabilize the binary that Fredriksen posits between ethnic Israel and Paul’s Gentiles-in-Christ as ethnic ‘other’. In the end, I demonstrate that Paul’s ethnic reconfiguration of Gentile identities resembles Philo’s proselyte discourse and is more disruptive ethnically than Fredriksen’s phrase ‘ex-pagan pagans’ would suggest.